UPAYA MENINGKATKAN PEMAHAMAN KONSEP SUSUNAN PEMERINTAHAN DESA DAN KECAMATAN MELALUI METODE CONCEPT MAPPING PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN SISWA KELAS IV SDN GENENGSARI I KEMUSU BOYOLALI - Dewi Indah Rahmawati; Al Sugijanto (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this research is to improve the comprehension of the â€œPemerintahan Desa dan Kecamatanâ€ using learning methods Concept Mapping fourth grade students of State Elementary School Genengsari 1. This research uses class action research that is held in two cycle. The data was gained from observation result, interview and test. The research result show, Concept Mapping method can increase comprehension of concept Civic Education. It looks of enhancement comprehension of student Civic Education concept that has reached KKM 70. At the first cycle, there is an improvement that is from pre-action around 19% or 5 students become 58% or 15 students at the end of first cycle. At the second cycle also has improvement that is from 58% or 15 students at the first cycle become 96,2% or 25 students at the end of second cycle. Therefore could be said that this class action research is successful to increase the comprehension of Civic Education concept fourth grade students of State Elementary School Genengsari 1 because has meet the successfully criteria that specified with shown 80% of the number of students have reached Minimum Completeness Criteria (KKM).